From Theoretical To Practical: Developing Tillich’s Apologetics - Morrison, Wendy (Lumen et Vita, 2011)
Paul Tillich’s understanding of faith, doubt, and church communities forms part of a systematic theology which Tillich understands as a theoretical apologetics. By developing these themes, especially Tillich’s concept of existential doubt, five guidelines for a practical apologetics can be developed in line with Tillich’s theoretical apologetics. First, both believers and nonbelievers are included in the apologist’s audience because both are at risk of idolatry. Second, the goal of apologetics is to end the suppression of doubt in order to break down idols. Third, this apologetics affirms faith without aiming to rid one of doubt. Fourth, apologetics should bring Christians and non-Christians into faith communities. Fifth, those faith communities should continue the work of apologetics by remaining open to doubt. These guidelines form a method of apologetics that speaks to the increasing secularity of the world. By breaking down traditional categories which separate faith from doubt and believers from nonbelievers, this practical apologetics is capable of moving people toward a deeper, more dynamic faith in the True God.